Factors Related to Breast Self-Examination Behavior (SADARI) of University of Muhammadiyah Surakarta Students - Fatihah, Ainaya; Setiyadi, Noor Alis (JURNAL KESMAS DAN GIZI (JKG), 2025)
One of the leading causes of cancer deaths in women worldwide is breast cancer. It is imperative to improve understanding of the various aspects of early detection and prevention so as to identify problems early enough to reduce breast cancer deaths. Early detection by the method of breast self-examination (SADARI) is a preventive and effective step in reducing the incidence of death due to breast cancer. The purpose of this study was to determine the factors associated with breast self-examination behavior (SADARI) in female students of Universitas Muhammadiyah Surakarta. This study used an observational method with a cross-sectional design. The research sample amounted to 263 respondents selected using insidental sampling technique. The results there was a relationship between knowledge (0.000) and attitude (0.010) with breast self-examination behavior (SADARI). However, there was no relationship between family support (0.587) and information exposure (0.623) with breast self-examination behavior. The conclusion of this study emphasizes the importance of increasing education and socialization about SADARI for female students in order to increase awareness and implementation of SADARI behavior as an early prevention measure for breast cancer.